Intentional Versus Incidental Inclusion: A Comparative Analysis of Enat Bank and Addis International Bank in Advancing Women’s Economic Empowerment through Microfinance in Ethiopia - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
This review article presents a comparative analysis of two Ethiopian commercial banks—Addis International Bank (AdIB) and Enat Bank, examining their respective approaches to women's economic empowerment through microfinance. Ethiopia presents a striking paradox: women own the majority of micro and small enterprises yet face a 19-percentage-point gap in account access and are 1.5 times less likely to receive formal loans than men. Closing these gender gaps could increase Ethiopia's GDP by an estimated US3.7 billion annually. Using institutional theory, feminist economics, and the capability approach as analytical frameworks, this review contrasts AdIB's incidental inclusion model, broad-based financial access without gender-specific mechanisms, with Enat Bank's intentional inclusion model, gender-led governance, collateral-free lending, and targeted non-financial services. The analysis reveals that Enat Bank's approach produces superior empowerment outcomes, demonstrated by its